Vasco Ronchi Colloquia: vision on Technology Transfer - AAVV, AAVV (Il Colle di Galileo, 2023)
The National Institute of Optics has launched an event format for the dissemination of research results aimed at an entrepreneurial audience: the Vasco Ronchi Colloquia (VRC). The VRCs are focused on research results suitable for a technology transfer path and have been named in memory of the illustrious founder of the Institute, physicist Vasco Ronchi. This report presents the formula devised for the VRCs and an in-depth analysis of the topics covered by the first VR Colloquium, held on April 3rd 2023 at the Arcetri headquarters of the CNR-INO.